Contribution of Bangladesh College of Physicians and Surgeons to Health Sector and Medical Education in Bangladesh: A 50-year Perspective - Amiruzzaman, -; Robed Amin, Mohammad; Tanvir Islam, Mohammad; Kumar Dey, Sanjoy; Islam, Naylla; Giti, Susane; Rahman, Md Mizanur; Afrose, Salma; Rahman, AKM Fazlur; Islam, Md Nazrul; Alam, ABM Khurshid; Faiz, Md Abul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Bangladesh College of Physicians and Surgeons (BCPS) was established in June 1972 through an Order revised in 2018 as an act with six functions which cover post-graduate education of all specialties of medical science. This commission report is to document the spectrum of contribution of BCPS in the health and education sector through its fellows and members. The data obtained for this report covers selected literature review, consultation with key official documents- Year Book of BCPS, Annual report of honorary secretary of BCPS, Health Bulletin of DGHS, various website, information from a brief quick Google survey on the fellows and focus group discussion (FGD) with senior present and past leaders of BCPS. BCPS is providing a skill based supervised comprehensive logbook based clinical training of five years’ duration through its recognized/accredited hospitals in different tiers of mostly public health system across the country. While undergoing clinical training the ‘would be fellows’ provide supervised quality clinical services to the patients attending the BCPS accredited hospitals. BCPS is producing specialists’ human resources by offering fellowship covering general and specialized subjects (n=59) and membership (n=16) in various branches of medicine. Immediately after independence there were 247 specialists altogether in the country. Since its inception, in 1972 after the liberation, 8266 fellows are entered as fellows, 7887 fellows with examinations, 111 without examinations and 268 honorary fellows; 3222 are entered as members of the College. The fellows of BCPS are engaged in providing specialized patient care in various fields of medical science as professor, associate professor, assistant professor and consultants in various public and non-government medical college hospitals, medical universities, post-graduate institutes, district hospital, and upazila health complexes. As a teacher most of the fellows are also heavily engaged in human resource development at both under-graduate and post-graduate level. Through their active voluntary engagement, the fellows of the College participate in the core activities of the College for HR development through activities related to monitoring & supervision, assessment, continuous professional development, skill development of the trainees and the fellows. Fellows are equally contributing in the armed forces medical services as clinical and para clinical specialists and development of specialist HRs. Additionally, fellows are contributing to various aspects of important public health topics relevant for SDG and Bangladesh. Fellows are also engaged in doing funded and non-funded quality researches and writing of scientific intellect at national and international publication system. Having achieved the various positions in academic, research and administrative arena BCPS fellows’ role in policy development and implementation, and scientific development deserve special appreciation. Future contribution of BCPS should prioritize quality assurance strategy for training-learning, enrich effectiveness of examination system, effective branding of BCPS, increase allocation and creating a conducive environment for conducting research. Conclusion: The glorious contribution of BCPS in the development of quality specialist health human resources over the last 50 years attained almost a self-sufficiency. Further ensuring quality assurance in training learning of future fellows and continued advanced training of the newly qualified fellows will help in branding of BCPS and technology transfer saving government exchequer. J Bangladesh Coll Phys Surg 2022; 40: 5-18